Hit or Myth?: Methodological Considerations in Comparing Dionysos with the Johannine Jesus - King, Fergus J. (Biblical theology bulletin, 2021)
The relationship between Dionysiac and emerging Christian traditions has long exercised biblical and classical scholars. Dionysianism is complex because of both its constituent mythologies and the fluidity and variety of its rituals. Emerging Christianity similarly defies a single metanarrative. This essay notes the difficulties of comparing Dionysiac tradition with just one early Christian text: the Gospel of John. The variety of Dionysiac material, the particular issues raised by critical readings of the Gospel (content and composition), the difficulty of overarching theological terminology (like “sacramentalism”), intertextuality, and mimesis criticism are all problematic when comparing the two traditions and their texts.